Sudden Stops and Exchange Rate Strategies in Latin America - Arturo Galindo; Alejandro Izquierdo (Inter-American Development Bank, Research Department, 2003)
An examination of several case studies in the region suggests that the ability to sustain a credible monetary policy depends on how vulnerable countries are to the impacts of sudden stops. In this respect, four aspects are of vital importance to ameliorate such impacts. Opening up the economy so that there is an increased supply of tradables will reduce the size of the fall in tradable absorption that is typically required by a sudden stop. Reducing the level of indebtedness will ensure that the required RER depreciation will be smaller. Lowering currency mismatches in the composition of debt relative to the composition of output will reduce vulnerability to valuation effects. Finally, the exposition to possible fiscal contingencies should also be addressed to reduce vulnerability of fiscal accounts, such as costly bank bailouts that stem from currency mismatches in the financial sector.
Keywords: 330; Wechselkurs; Kaufkraftparität; Kapitalmobilität; Wechselkurssystem; Geldpolitik; Öffentliche Schulden; Lateinamerika